The effectiveness of divalent cation addition for highly saline activated sludge cultures: Influence of monovalent/divalent ratio and specific cations - Raghavendran Sivasubramanian (16931775) (2021)
Saline wastewaters are prevalent in various industries and pose challenges to stable biological treatment. Increasing monovalent cation concentrations are commonly reported to deteriorate treatment and settling performance, while divalent cations can enhance flocculation and settling. However, many previous studies were performed at relatively low salinities and reports conflict on whether concentrations of monovalent cations, divalent cations, or their ratio (M/D) are most critical. This study investigates whether addition of divalent cations shows the same benefits at high salinity (~40 g NaCl.L-1 ) and whether divalent ion concentration or M/D is a better predictor of enhancement. Nine sequencing batch reactors were operated at 0.8 M NaCl or KCl monovalent salt concentration, and the concentration of divalent cations (Ca2+ and Mg2+) was varied. M/D was found to be the critical factor that consistently influenced sludge characteristics. It was particularly important in describing hydrophobicity, sludge volume index (SVI) and specific oxygen uptake rate (SOUR), with rpartial of 0.879, 0.971 and 0.966 respectively in models that had an r2adj greater than 0.93. Lower M/D also increased biomass concentrations and reduced extracellular polysaccharides, the latter which in turn correlated strongly with many shape and surface charge measures. The specific monovalent salt (Na+ or K+) influenced treatment performance, biomass concentrations, hydrophobicity, SOUR, extracellular protein and SVI. The specific divalent cation was only important in describing SVI, where Mg2+ was beneficial. Overall, this study shows that addition of divalent cations can greatly benefit high salinity activated sludge systems by improving the sludge structure, settling and organic removal. Other Information Published in: Chemosphere License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.chemosphere.2021.129864